Analysis of Construction Principles of Fifth Generation Mobile Communication Networks (5G) - Hasanov, M.H.; Mammadov, F.H. Mammadov; Orujova, M.Y. (Herald of Azerbaijan Engineering Academy, 2024)
The article provides an overview of a number of scientific publications related to 5G networks in the last five years and analyzes the main technologies used in these networks. The 5G networks themselves have developed a structure that includes two planes, such as softwarebased implementation of functions and standard commercial equipment, as well as their architecture consisting of control and user planes. In order to expand the structure and architecture of these networks, their vector models have been proposed.